The Role Of Coagulation Testing Prior To Surgery - Cozie, Novie Amelia; Windiastuti, Endang; Gatot, Djayadiman (Lingkar Studi Bedah Plastik Foundation, 2012)
Preoperative coagulation screening has been among the most debated of all laboratory tests, especially in children. Although an undiagnosed coagulopathy could result in serious surgical morbidity, commonly used screening tests such as bleeding time, prothrombin time, activated partial thromboplastin time, and platelet count, do not reliably predict abnormal perioperative bleeding. Laboratory testing should be considered in patients either the history or medical condition suggests a possible hemostatic defect, in patients undergoing surgical procedures that might induce hemostatic disturbances (eg, cardiopulmonary bypass), when the coagulation system is particularly needed for adequate hemostasis (eg, tonsillectomy), and in patients for whom even minimal postoperative bleeding could be critical (eg, neurosurgery). In the case of minor surgery and a negative history of clotting disorders, no tests are suggested.